2004
DOI: 10.1096/fj.03-0773fje
|View full text |Cite
|
Sign up to set email alerts
|

Injury‐induced NF‐κB activation in the hippocampus: implications for neuronal survival

Abstract: Nuclear factor (NF)-kappaB p50 protein is involved in promoting survival in hippocampal neurons after trimethyltin (TMT)-injury. In the current study, hippocampal NF-kappaB activity was examined and quantitated from transgenic kappaB-lacZ reporter mice after chemical-induced injury. NF-kappaB activity was localized primarily to hippocampal neurons and significantly elevated over that in saline-treated mice between 4 and 21 days after TMT injection. Seven days after TMT injection, a timepoint of elevated NF-kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 113 publications
(94 reference statements)
5
21
0
Order By: Relevance
“…In line with our findings, the ␥ subunit was identified recently by DNA microarray analysis in the mouse hippocampus after chemical injury induced with trimethyltin, the drug causing mitochondrial dysfunction (59). Although no information is available about which splice form of ␥ was expressed, we hypothesize that induction of ␥a and the subsequent inhibition of the Na,K-ATPase activity might favor neuronal cell survival during energy deficiency and would be adaptive to sustain apoptotic insult.…”
Section: Discussionsupporting
confidence: 89%
“…In line with our findings, the ␥ subunit was identified recently by DNA microarray analysis in the mouse hippocampus after chemical injury induced with trimethyltin, the drug causing mitochondrial dysfunction (59). Although no information is available about which splice form of ␥ was expressed, we hypothesize that induction of ␥a and the subsequent inhibition of the Na,K-ATPase activity might favor neuronal cell survival during energy deficiency and would be adaptive to sustain apoptotic insult.…”
Section: Discussionsupporting
confidence: 89%
“…Regulation by NF-B could also be indirect. NF-B complexes are involved in the control of a number of cellular responses during inflammatory and degenerative responses, and NF-B signaling regulates the transcription of a variety of genes that play potential roles in inflammatory reactions and neuronal survival after injury (19,(47)(48)(49). We further showed that inhibition of NF-B activation resulted in a significant reduction (ϳ50%) of CCL2 gene expression in lesion-reactive hippocampi.…”
Section: Discussionmentioning
confidence: 82%
“…Finally, FXYD2a but not FXYD2b expression is induced in renal cells of proximal origin as well as in several cell lines of other than renal origin by hypertonicity, heat shock, and chemical stress (98). Moreover, injury-induced NF-B activation induces FXYD2 expression in the hippocampus (48). FXYD2a induction in cells of renal origin is accompanied by a reduction in Na-K-ATPase activity and in the rate of cell division (98).…”
Section: F244mentioning
confidence: 99%